Thermodynamic Properties of Free Standing Thin Metal films Investigated Using Statistical Moment Method: Temperature and Pressure Dependence - Hung, Vu Van; Phuong, Duong Dai; Hoa, Nguyen Thi (Communications in Physics, 2014)
The moment method in statistical dynamics (SMM) is used to study thermodynamic properties of free standing thin metal films with face-centered cubic structure (fcc) taking into account the anharmonicity effects of the lattice vibrations and hydrostatic pressures. The explicit expressions of the lattice constant, thermal expansion coefficient, and specific heats at the constant volume and those at the constant pressure, \(C_V\) and \(C_P\) of the metal thin films are derived in closed analytic forms in terms of the power moments of the atomic displacements. The thermodynamic quantities of Au, Ag, Cu and Al metal thin films are calculated as a function of the temperature and pressure, and they are in good agreement with the corresponding results obtained from other theoretical calculations and experimental values. The effective pair potentials work well for the calculations of fcc metal thin films.